Literasi Al-Qur’an Melalui Taman Pendidikan Al-Qur’an Di masa Pandemi Covid-19 - Abdul Halim, Abdul Karim Halim (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2022)
This study aims to determine Al-Qur'an Literacy through the Al-Qur'an Education Park in the Covid-19 Pandemic Period. The research method uses qualitative methods with a qualitative case study approach. The method is implemented because this research is related to social society. To collect data, in-depth interviews were used. Qualitative research is research without mathematical value. Meanwhile, the main source of information for this research came from the Al-Qur'an Education Park or TPA. The results of the study show that the Covid-19 pandemic has affected the learning process in non-formal institutions, namely the Al-Qur'an Education Park, Al-Qur'an Education Park (TPA) facing many obstacles and changes in the process of Al-Qur'an literacy education in Indonesia. the time of the Covid-19 pandemic.